Kesalahan Tatabahasa Bahasa Melayu dalam Penulisan Karangan Pelajar (LSP International Journal, 2018)
This study was conducted to analyse the grammatical mistakes – errors made by Indonesian students when learning Bahasa Malaysia Academic Writing at Universiti Teknologi Malaysia. Students essay writing were used/utilised as the primary data in locating to identifies grammatical mistakes made. It was found that Indonesian students made many grammatical mistakes or various aspects such as semantic and morphology. The mistakes on morphology aspects were normally the word choice, preposition and pronouns. Further discovery finding revealed that the reasons for mistakes made were because lack of knowledge in Bahasa Malaysia language and confusion on the meaning of words. Eventhough Malay language originates from the same language as the mother tougue of the students but there are actually many diffrences which lead to uncertainly of the Indonesian students in the use of the language.